Experimental investigation on the wave performance with the interference of floating aquaculture cages in single and tandem arrangements. (15th October 2022) - Ma, Chao; Zhao, Yun-Peng; Xu, Zhijing; Bi, Chun-Wei
Abstract: Floating aquaculture cages deployed in the nearshore affect the wave field and contribute to the coastal defense by damping incoming waves. Most pioneering works concerning aquaculture cages have concentrated on the hydrodynamics of the structures instead of their influence on the wave field. In order to bridge the gap, this paper examines the wave performance with the interference of floating aquaculture cages via physical model tests. The results show that the existence of cages increases wave height on the weather side. The wave-dissipation performance of the net cage is closely related to the ratio of the wavelength to the structural span, and the minimum transmission coefficients appear in the conditions with the maximum wave number. Moreover, the crests of the free surface elevation inside the floating frames are almost flat, which is particularly obvious in the long-period wave conditions. The surface elevations show nonlinearity in small-wavelength conditions, which is dominantly caused by the pitch motion of the cages. Nevertheless, the presence of the cage does not affect the phase differences in the wave elevation at different positions. The nets have an opposite effect on wave response inside the cage under the conditions of long-period and short-period waves. Highlights: The wave performance with the interference of floating aquaculture cages are examined via physical experiments. The wave transmission coefficients were closely related to the ratio of the wavelength to the structural span. The wave surface elevations inside the floating frames showed nonlinearity under small wavelengths. The nets had an opposite effect on the wave response inside the floating frame in long- and short-period waves.